Optimisation of a sample preparation method for the determination of fumonisin B-1 in rice - Petrarca, Mateus Henrique [UNESP]; Rodrigues, Maria Isabel; Rossi, Elizeu Antonio [UNESP]; Sylos, Célia Maria de [UNESP] (Elsevier B.V., 2014)
A simple, rapid and cost-effective sample preparation method for the determination of fumonisin B-1 in rice was optimised using a strategy of sequential experimental designs. Initially, a Plackett-Burman design was applied to select the statistically significant variables for the determination of fumonisin B-1, and then, a central composite rotatable design was used to define the optimal conditions of these variables. The method involves extraction with a 50% acetonitrile aqueous solution and glacial acetic acid, liquid-liquid partitioning with addition of anhydrous sodium sulphate and sodium chloride, followed by dispersive SPE clean-up with diatomaceous earth. The final extract was analysed by HPLC-FLD after precolumn derivatisation with ortho-phthaldialdehyde. The optimised method was validated for selectivity, linearity, matrix effect, limits of detection and quantification, trueness, and precision, and then applied to commercial samples of polished rice. This is the first report of the occurrence of fumonisin B-1 in commercial samples of polished rice from the Southeast region of Brazil. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Fumonisin B-1; Rice; Sample preparation; Plackett-Burman design; Response surface methodology; In-house validation